Identify the Location of the Camp of Religious Tourism and Leisure City With AHP and Fuzzy Logic in GIS (The holy city of Qom) - Mehdi Gharakhlou; Mostafa tavakoli naghmeh Tavakoli naghmeh; Alireza Garousi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2020)
Today, the tourism industry has been considered as one of the important sources of income in the global economy. Religious tourism is one of the divisions of the tourism industry in which the Muslim world especially in Iran is important. Qom- a city with religious, cultural, historical, and natural capabilities- as the Incarnational Religious Base of Shiism known as one of the most important pilgrimage centers in the Muslim world. Every year, many tourists from inside and outside the country travel to this city. Due to the religious importance of this city, the most important part of the pilgrims of this city is religious tourists. A high volume of tourists requires proper infrastructure and facilities for settling, accommodating, and spending leisure time. The present research according to purpose is applied one, in terms of the method is descriptive, and data have been collected based on desk resources. to identify the appropriate areas for the construction of leisure and recreational camps and respond to the needs of pilgrims and tourists in this city, Firstly, criteria and sub-criteria weighting is done by using the hierarchy model; finally, appropriate areas, area 3, 2, 8, and 4, at the regional level are introduced by using GIS